Congenital smooth muscle hamartoma. - Larralde de Luna, M.; Pizzi de Parra, N.; Santos Muñoz, A.; Parra, C.; Parra, V.; Moreno, S.; Popi, G.; Schroh, R. (European Journal of Pediatric Dermatology, 2018)
We present five cases of children with congenital smooth muscle hamartoma. It is a distinct clinical and histological entity characterized by a slightly hyperpigmented plaque with proliferation of smooth muscle within the reticular dermis. Congenital smooth muscle hamartoma is not associated with systemic involvement or poor prognosis. This kind of lesion usually becomes less prominent with time and no treatment is necessary.